LITERASI SAINS DALAM PEMBELAJARAN BERBASIS MASALAH (Penelitian Pre-experimental terhadap siswa kelompok atas, tengah, dan bawah SDN Waringin II dan SDN Palasah I di Kecamatan Palasah Kabupaten Majalengka pada Materi Energi Panas) - Nurjanah, Aan; Sudin, Ali; Sujana, Atep (Jurnal Pena Ilmiah, 2017)
This research is based on the result of the research in PISA 2015 that science literacy on students is still low. Indonesia that ranked 69 from 76 countries with the average score is still 403 and it means in above average of international score that has 493. One of learning that can increase science literacy on students is problem based learning. It uses the learning that base on problem and the differences of the increasing scale of students’ behavior on science. The method and design in this research uses pre-experimental method and one group pretest-posttest design. The population in this research are 4th grade elementary students in Kecamatan Palasah with the subjects are from SDN Waringin II and SDN Palasah I. The result of the research shows that learning that based on problem can advance students’ science literacy on those three groups. However, there are the differences the increasing level on those three groups and also the difference of the increasing scale on those three groups.